Computer simulation of thromboexclusion of the complete aorta in the treatment of chronic type B aneurysm. (January 2013) - Filipovic, Nenad; Nikolic, Dalibor; Saveljic, Igor; Djukic, Tijana; Adjic, Oto; Kovacevic, Pavle; Cemerlic-Adjic, Nada; Velicki, Lazar
<x xml:space="preserve">Abstract</x> The purpose of this computational study was to examine the hemodynamic parameters of the velocity fields, shear stress, pressure and drag force field in the complex aorta system, based on a case of type B aortic dissection. The extra-anatomic reconstruction of the complete aorta and bipolar exclusion of the aneurysm was investigated by computational fluid dynamics. Three different cases of the same patient were analyzed: the existing preoperative condition and two alternative surgical treatment options, cases A and B, involving different distal aorto-aortic anastomosis sites. The three-dimensional Navier-Stokes equations and the continuity equation were solved with an unsteady stabilized finite element method. The aorta and large tube graft geometries were reconstructed based on CT angiography images to generate a patient-specific 3D finite element mesh. The computed results showed velocity profiles with smaller intensity in the aorta than in the graft tube in the postoperative case. The shear stress distribution showed low zones around 0.5 Pa in the aneurysm part of the aorta for all three cases. Pressure distribution and, particularly, drag force had much higher values in the preoperative aneurysm zones (7.37 N) than postoperatively (2.45 N), which provides strong evidence of the hemodynamic and biomechanical benefits of this type of intervention in this specific patient. After assessing the outcome obtained with each of the two alternatives A and B, for which we found no significant difference, it was decided to use option A to treat the patient. In summary, computational studies could complement surgical preoperative risk assessment and provide significant insight into the benefits of different treatment alternatives.